ANALISIS KEPATUHAN KARYAWAN TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI PT. KEBON AGUNG UNIT PG. TRANGKIL PATI - Faddila Purna Dewi; Ekawati Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Personal Protective Equipment (PPE) is a tool used workers to protect themselves from potential hazards and accidents that might occur in the workplace. PT. Kebon Agung Unit PG. Trangkil have some Occupational Safety and Health (OSH), one of which is a PPE program. Approximately 80% of employees do not use the production section in full PPE when working. This study aims to describe and analyze the level of compliance of employees in applying the PPE program. This research uses descriptive method with qualitative approach. Key informants in this study as many as 11 people and 3 people as informants triangulation. The results showed employees have good knowledge about PPE. PPE socialization program held annually at the start of the milling season. PG. Trangkil already provide PPE are complete and free of charge to all employees. When the milling season supervision by supervisors OSH is not done routinely and tight, so many employees who violate the rules. All employees have a positive response regarding PPE program. Hot environment makes employees feel uncomfortable when using PPE. There is no reward and punishment program for PPE program. Reward that there is a reward for the performance of employees and service period. While the punishment was limited to verbal warning and not lead to sanctions. The company needs to increase socialization, supervision, punishment and reward to the sustainability of the program.